The Effect Of Government Expenditure On Islamic Human Development Index - Nisful Laila, Sri Herianingrum, Muhammad Nafik H, Qudsi Fauzi, Fairuz Ulfa Afifa, (Opción, 2019)
This research aims to determine the effect of government spending and unemployment on IHDI in Indonesia in 2010-2013. The method of analysis used in this research is regression analysis of fixed effect model (FEM) panel data. The result of t-test in this research indicates that government expenditure has a significant positive effect on IHDI and unemployment has a negative effect not significant on IHDI. In conclusion, the two variables have a significant effect on IHDI in Indonesia in 2010-2013.